The Significance of Antitrinitarian Translations of the Bible into Polish in the Dialogue between the Polish-Lithuanian Commonwealth, Eastern and Western Europe - Pietkiewicz, Rajmund (Verbum Vitae, 2023)
The author of this essay poses the question about the significance of antitrinitarian translations of the Bible into Polish for the exchange of ideas and achievements of science between Eastern and Western Europe in the second half of the sixteenth and first half of the seventeenth centuries. In an attempt to systematize various facets of this significance, the author will deal with the bibliographical and bibliological aspects of the editions of the Bible in the Polish language, the dynamics of the development of Polish antitrinitarian biblical translations and biblical editing against the background of the history of the Polish Brethren in the Polish-Lithuanian Commonwealth, the sources of the translations and the influence they exercised in the territory of the Polish-Lithuanian Commonwealth and abroad. The author’s research made it possible to identify two directions of the exchange of ideas. The first direction is the reception in Central and Eastern Europe of the achievements of Western biblical philology and exegesis. The second is related to the Polish Brethren’s contribution to Western Europe’s science and culture. Particularly noteworthy here is the voice of Polish Antitrinitarians in the field of research into the criticism of the biblical text, although this impact was limited due to the language barrier. Of much greater importance were the translations of the Polish Brethren in the East (the Grand Duchy of Lithuania and the Muscovite lands), where the language barrier was less significant. They also popularized the philological and exegetical achievements of the West among the Karaites and Tatars of the Grand Duchy of Lithuania.